Efektivitas Undang-Undang No. 35 Tahun 2009 dalam Tindak Pidana Narkotika - I Putu Suputra; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
Currently, drugs in Indonesia are very rampant. The negative impact caused is enormous. Supervision and control as an effort to eradicate and prevent the circulation of narcotics are indispensable for crimes in this field that continue to develop in terms of quality and quantity which lead to the destruction of the nation's new generation. This research was conducted with the aim of describing the application of sanctions against narcotics crimes in decision Number 564/Pid.Sus/2018/PN.DPS and the judge's consideration on the application of sanctions in the Narcotics Crime Decision in Decision Number 564 / Pid.Sus/2018/PN.DPS. This research used a normative legal research method. The results of this study indicated that the application of narcotics criminal sanctions, especially in decision number 564/Pid.Sus/2018/PN.DPS is in accordance with what is stipulated in Law No. 35 of 2009 concerning Narcotics with various articles of bondage and strict laws in accordance with the evidence as evidence of the government's seriousness in providing a deterrent effect, safeguarding, overcoming, and saving or protecting a nation from the dangers of narcotics. In addition, the judge's consideration in making a decision on narcotics crime in decision number 564/Pid.Sus/2018/PN.DPS is in accordance with the evidence, where proof requires at least 2 (two) evidence to consider a fact that is in the trial and is assisted by a judge's decision who will later decide on a case.